Antioxidant enzyme and malondialdehyde levels in patients with panic disorder - Kuloglu, M; Atmaca, M; Tezcan, E; Ustundag, B; Bulut, S (Karger, 2002)
There is evidence of an etiopathogenetic role of free radicals (FRs) in some neuropsychiatric disorders. The aim of the present study was to determine whether the activity levels of some antioxidant enzymes [glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and catalase (CAT)] and malondialdehyde (MDA), a product of lipid peroxidation, were associated with panic disorder (PD). Twenty patients diagnosed with PD and 20 healthy controls were enrolled in this study. A clinical evaluation and measurements of GSH-Px SOD, CAT and MDA were performed. Additionally, all patients were assessed by the Panic Agoraphobia Scale (PAS). The mean GSH-Px, SOD and MDA levels of the patient group were significantly higher than those of the controls. There was a significant positive correlation between PAS scores and GSH-Px, SOD and MDA levels and between the duration of illness and SOD, CAT and MDA levels in the patient group. In conclusion, our results suggest that FRs may be involved in PD. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: panic disorder; antioxidant enzyme; malondialdehye